Estudo químico dos extratos e frações com atividades antiúlcera e antimicrobiana das folhas e raízes de Helicteres sacarolha A. ST. HIL. (Malvaceae) - Faria, Washington Ferreira (2016)
The Helicteres genus is distributed in the pantropical region, with about 60 species. The center of diversity of this genus is in Brazil, where there are about 31 species. A huge variety of Helicteres are used in medicinal funtions, where a huge amount of compound has been isolated with a variety funtions, such as anti-inflamatory, analgesic, anti-bacterial and anti-diabetic activities, among others. This wide utilization of this genus for medicinal purposes should be because of the variety of special metabolites, such as: lignans, neolignans, sesquiterpenes, triterpenes, quinones, alkaloids, flavonoids, saponins, tannins and coumarins. Popularly known as "sacarolha" or "rosquinha", Helicteres sacarolha root are used in tea form in folk medicine as depurative and syphilitic inflammation. Previous studies made by the Laboratory of Pharmacology of Natural Products at UFMT shows promising effects of the hydroethanolic crude extract of H. sacarolha for antiulcer activity, showing up, therefore, a promising candidate for phytotherapy. Motivated by this result, farmacological studies observed in the scientific literature and the shortage of chemical studies, this work aims to lead to chemical and pharmacological studies for isolation and identification (s) fraction (s)/substance (s) with potential activities anti-ulcer / antimicrobial from leaves and roots of H. sacarolha. The plant material (leaves and roost) was collected on April 30, 2014, in the municipality of Nossa Senhora do Livramento. The extract were obtaneid by cold extraction with EtOH/H2O (7:3) and submitted to chromatographic analysis, leading to the isolation of 6 compound: a mixture of steroids, β-sitosterol (19) and stigmasterol (59), two flavonoids, kaempferol (57) and trans-tirilosíde (58), a derivated fenolic, ethyl p-cumarate (56) and vanilic acid (60). The antiulcer activity of EBHEF was evaluated in the farmacological laboratory at UFMT, and the extract showed activity similar to standard pharmacologic (carbenoxolone) at a dose of 100mg/Kg. The crude extracts and fractions of the roots and leaves were evaluated for antimicrobial assays by the research group of the University of Cuiabá (UNIC), and the samples reveal to be active for antifungal activity a variety of Candida sp. (MIC 15,6 μg/mL) and Cryptococcus neoformans (MIC 62,5 μg/mL).